2018
DOI: 10.1142/s1793984418400019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Built Environment on Respiratory Health: An Empirical Study

Abstract: In many heavy industrialized countries such as China and India, the impact of air pollution on respiratory health has been headline news in recent years. Among the risk issues examined, exposure to particulate matter (PM) is cited as the prime contributing factor that causes respiratory diseases, yet it is traceable and controllable. In this paper, we report on an empirical study conducted in Shanghai, based on urban spatial determinants as independent variables to investigate its link to occurrence of lung ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Jacobs suggested a minimum density of 175 dwellings per hectare to arrive at a vital and diverse urban landscape. 135 The emphasis on urbanity as an attractive part of city life fit in well with two problems that cities were confronted with in the 1980s: competition with suburbia, and a general degeneration of city economies as a result of recession and de-industrialization. Cities reinvented their identities in what, somewhat tautologically, was seen as the essence of the city: urbanity.…”
Section: Dutch Density Developmentsmentioning
confidence: 83%
See 1 more Smart Citation
“…Jacobs suggested a minimum density of 175 dwellings per hectare to arrive at a vital and diverse urban landscape. 135 The emphasis on urbanity as an attractive part of city life fit in well with two problems that cities were confronted with in the 1980s: competition with suburbia, and a general degeneration of city economies as a result of recession and de-industrialization. Cities reinvented their identities in what, somewhat tautologically, was seen as the essence of the city: urbanity.…”
Section: Dutch Density Developmentsmentioning
confidence: 83%
“…131 Negative impact of density on physical health is reported in four studies that indicate increased heat vulnerability, 132 a higher death rate in relation to epidemics, 133 lower fertility rates 134 and a higher risk for lung cancer. 135 However, in relation to the latter, another study reported that density had no impact. 136 This study investigated many external factors, establishing that it is traffic and not density that plays a significant role in predicting lung cancer incidence.…”
Section: Density and Physical Healthmentioning
confidence: 98%
“…A negative impact of density on physical health is reported in four studies that indicate increased heat vulnerability (Kim & Ryu 2015), a higher death rate in relation to epidemics (Li et al 2018), lower fertility rates (Sato 2007) and a higher risk for lung cancer (Xu et al 2018). Wang et al (2016) showed, however, that it is traffic and not density that plays a significant role in predicting lung cancer incidence.…”
Section: Density and Healthmentioning
confidence: 99%